Evaluation of novel methods of assessments in pharmacology to develop new attitudes and skills in Caribbean Medical School - Beedimani, Ravindra S.; Shetkar, Shivkumar G. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Assessment is said to drive student learning and define the curriculum. The problem-solving type of multiple choice questions (MCQs), which can be used to probe and assess medical students in pharmacology should have a clinical vignette containing presenting complaints, abstract history, physical examination and laboratory data, followed by a single or series of questions based on it. National Board of Medical Examination (NBME), USA has an extensive bank of problem-solving MCQs, and these questions are often regarded as similar in format and focus to MCQs of United States Medical Licensing Examination (USMLE). The objective assessment of teaching and curriculum in this study is done by comparison of students’ performance in pharmacology comprehensive exam of NBME, USA before and after curriculum changes. This study was designed to obtain an objective assessment of teaching and curriculum by comparison of students’ performance in terms of student mean grades, percentage of students passed, percentage of students failed, percentage of students with honors, and individual highest scores of five semesters before and five semesters after curriculum changes in pharmacology comprehensive exam of NBME, USA among the 5th semester students of American University of the Caribbean, School of Medicine, St. Maarten. Methods: We have compared the students’ performance of pharmacology comprehensive exam of NBME using five parameters like student mean grades, percentage of students passed, percentage of students failed, percentage of students with honor, and individual highest score of five semesters May 2009, September 2009, January 2010, May 2010 and September 2010 semester batches before the introduction of curriculum changes with subsequent semesters January 2011, May 2011, September 2011, January 2012 and May 2012 semesters after the introduction of curriculum changes. Results: The pre-curriculum student performances were compared with post-curriculum changes using the Student’s t-test. The students mean scores improved significantly from 50.76 before curriculum changes to 56.54, students passed (%) increased from 94.57% before curriculum changes to 96.93% after curriculum changes and students with honors (%) increased significantly from 64.72% before curriculum change to 75.51% after curriculum changes and also seem to have remained consistently better. The students failed (%) decreased dramatically from 5.43% to 3.07% after curriculum changes. The highest individual mean score also improved significantly from 72.4 to 80.8 after curriculum changes and have remained consistent in the following semesters. Conclusions: There seems to be obvious improvements in student performance as reflected by a significant increase in mean scores, students pass (%), and students with honors (%) probably due to inclusion of problem-solving MCQs in formative and summative assessments in new curriculum compared with declarative MCQs in old curriculum. The student failed (%) decreased dramatically, which could be attributed to the changes in teaching content and format brought by curriculum changes in pharmacology. The teaching of pharmacology principles as pathophysiology of drug therapy also seemed to have prepared students better for NBME comprehensive exam and also USMLE Step 1. The clinical pharmacology exercises in small groups as role playing sessions seem to have really improved students’ comprehension and retention of the basic sciences knowledge for clinical application based on students’ feedback.